2017
DOI: 10.1021/acs.biomac.7b01136
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Styrene Maleic Acid Lipid Particles through RAFT

Abstract: The ability of styrene maleic acid copolymers to dissolve lipid membranes into nanosized lipid particles is a facile method of obtaining membrane proteins in solubilized lipid discs while conserving part of their native lipid environment. While the currently used copolymers can readily extract membrane proteins in native nanodiscs, their highly disperse composition is likely to influence the dispersity of the discs as well as the extraction efficiency. In this study, reversible addition-fragmentation chain tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 36 publications
2
68
0
Order By: Relevance
“…This is because peptide synthesis is sequential, whereas addition of carboxylate and other repeating units in amphipols and industrially prepared SMA polymers is randomly distributed along the polymer chain during assembly. Due to the ‘one-pot’ synthesis, these synthetic polymer preparations are often polydisperse mixtures of different lengths ( Popot, 2010 ; Smith et al, 2017 ). This compositional heterogeneity can be problematic for functional and structural studies ( Deller et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is because peptide synthesis is sequential, whereas addition of carboxylate and other repeating units in amphipols and industrially prepared SMA polymers is randomly distributed along the polymer chain during assembly. Due to the ‘one-pot’ synthesis, these synthetic polymer preparations are often polydisperse mixtures of different lengths ( Popot, 2010 ; Smith et al, 2017 ). This compositional heterogeneity can be problematic for functional and structural studies ( Deller et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our lab has shown that 3:1 styrene-maleic acid can be synthesized in a laboratory setting using reversible addition-fragmentation chain transfer polymerization (RAFT) polymerization and successfully used to characterize the structure of styrene-maleic acid copolymerlipid nanoparticles (SMALPs) 15,30 . RAFT polymerization is synthetically simple and provides flexibility to vary the structure of the polymer and influence the size of SMALPs 15,30 . SMALPs show compelling evidence that they are suitable for membrane protein incorporation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This analysis indicates that RAFT-SMA with alternating 3:1 subunit ratios are optimal for rapid and complete dissolution of synthetic liposomes into small discs, while larger protein complexes may be better solubilized by RAFT-SMA(2:1) polymers. A recent study of RAFT polymerization shows that greatest solubilization is achieved using a steep gradient of styrene and maleic acid monomers in a small (3kDa) polymer, while inclusion of a long homoblock of styrene is detrimental [20]. …”
Section: Introduction To Polymer-based Membrane Solubilizationmentioning
confidence: 99%